An improvement on the valiantbrebner hypercube data broadcasting technique / Nasaruddin Zenon - Zenon, Nasaruddin (Universiti Teknologi MARA Cawangan Pahang, 1990)
At the end of the writer's earlier article: A Model Solution for the Radar Surveillance Problem' [7] it is mentioned that a slight modification of the formulation given in the paper can be used to solve the problem of data broadcasting in multi processor computer system. The intended meaning of broadcasting there is the mannereach datum is distributed among the processors in a computer system. However, once the datum is processed by a particular processor it has to be passed to the next processor / s for further processing or to be combined with the whole data array (the broadcast procedure split the data set). This paper is motivated by a multi node broadcast technique for the hypercube architecture developed in 1982 by Valiant and Brebner [6] which the author feels can be further improved in terms of speed and performance. The writer tries to improve this algorithm because it is the only known algorithm for the hypercube machine that has the probability of more than i (log n) processors will simultaneously try to transmit a message through a given processor decreases exponentially with i. (Please refer to [4] for detail.)The arrangement of this paper is as follows. In section 1.0 a description of the hypercube topological characteristics will be given which can be used to modify the algorithm. Section 2.0 provides the description of the Valiant and Brebner (V-B) algorithm. In Section 3.0 we will propose a modification to the V-B algorithm. An analysis of the improved algorithm in comparison to te V-B algorithm is provided at the end of section 3.0.